2016
DOI: 10.1536/ihj.15-196
|View full text |Cite
|
Sign up to set email alerts
|

Low Stroke Rate of Carotid Stenosis Under the Guideline-Oriented Medical Treatment Compared With Surgical Treatment

Abstract: SummaryMedical treatment for asymptomatic carotid artery stenosis (ACAS) has advanced recently. The outcomes of medical treatment and surgical treatment were evaluated to clarify the optimal treatment for ACAS.Patients with ACAS of ≥ 50% luminal narrowing underwent serial follow-up carotid artery ultrasonography for one year or more at the Center for Cardiovascular Disease Prevention between November 2006 and October 2013. The incidence of cardiovascular events (stroke, myocardial infarction, cardiovascular de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…Carotid artery disease and cerebral microvascular disease have also been implicated. 35) In our study, minor neurologic complications were independently associated with the use of the Heartstring system. Although the patients in whom the Heartstring system was used had a higher rate of delirium, the difference in the incidence of minor neurologic complications was not statistically significant between the groups (P = 0.05).…”
Section: Discussionmentioning
confidence: 50%
“…Carotid artery disease and cerebral microvascular disease have also been implicated. 35) In our study, minor neurologic complications were independently associated with the use of the Heartstring system. Although the patients in whom the Heartstring system was used had a higher rate of delirium, the difference in the incidence of minor neurologic complications was not statistically significant between the groups (P = 0.05).…”
Section: Discussionmentioning
confidence: 50%
“…18,21,30,[32][33][34] In addition, it was reported that medical treatment is an important option for asymptomatic carotid artery stenosis compared with the surgical group, which included either CAS or CEA. 35) Because we observed a lower risk of stroke with CEA than with CAS, it would be meaningful to compare CEA with medical treatment in future studies.…”
Section: Discussionmentioning
confidence: 83%
“…After screening of 5915 unique reports and assessing the full texts of 231 for eligibility, we included 73 studies reporting 28 625 patients with ≥50% ACAS (Figure 1; Table S2). 8–10,16–85…”
Section: Resultsmentioning
confidence: 99%